ISOLATION AND PHYTOCHEMICAL TEST OF ANTICANCER ISOLATE OF SPONGE Hyrtios erecta - I Made Dira Swantara; Wiwik Susanah Rita; Rr Anisa Hernindy (Institute for Research and Community Services Udayana University, 2017)
AbstractThis research aims to isolate and phytochemically test of the toxic isolate from ethanol extract of the sponge Hyrtios erecta taken from the waters of Pari Island beach, Thousand Islands (Jakarta). Extraction of the sponges was carried out by 70% ethanol at room temperature. Partition and purification of the compounds were done by column chromatography with the stationary phase of silica gel and the mobile phase of n-hexane-chloroform (2:8). Toxicity screening test was done based on Bhrine Shrimp Lethality Test (BSLT). The compounds of the active isolate were performed by phytochemical test. Based on the results, it was found that the toxic isolate of Hyrtios erecta sponges has anticancer activity with IC50 of 30,497 ppm. The anticancer isolate contained alkaloid, steroid, and polyphenol compounds